Blood groups and their relationship with plasma levels of von Willebrand Factor - Márquez-Benítez, Yusselfy; Lancheros-Silva, Adriana María; Díaz-Chaves, Estéfani (Universidad y Salud, 2019)
Introduction: The type of blood group among other factors influences the plasma levels of von Willebrand Factor (FvW) and its biological activity could influence the development of thrombotic and hemorrhagic events. Objective: To describe the characteristics and mechanisms of post-translational reactions of the blood group that generate variation in the plasma concentration of FvW. Materials and methods: A descriptive theoretical review of documentary type. The databases consulted were Medline, Lilacs, ScienceDirect, Scopus, SciELO, Proquest, Ovid and Pubmed. As a selection criterion, articles in English and Spanish were included beginning in 2010 and some previous ones as historical reference. Results: The main mechanisms and investigations that show the influence of the ABO blood group type on the plasma levels of FvW, as well as the structure and function of this protein were described. Conclusions: FvW plasma concentrations may depend on the type of blood group, age, sex, pregnancy, menstrual cycle, protein variation and biochemical and immunological factors. The type of blood group of patients could be considered as a possible future predictor of both thrombotic and hemorrhagic clinical complications.